2021
DOI: 10.1167/tvst.10.7.28
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Pachychoroid on Optical Coherence Tomographic En Face Images Using Deep Convolutional Neural Networks

Abstract: To study the efficacy of deep convolutional neural networks (DCNNs) to differentiate pachychoroid from nonpachychoroid on en face optical coherence tomography (OCT) images at the large choroidal vessel.Methods: En face OCT images were collected from eyes with neovascular age-related macular degeneration, polypoidal choroidal vasculopathy, and central serous chorioretinopathy. All images were prelabeled pachychoroid or nonpachychoroid based on quantitative and qualitative criteria for choroidal morphology on mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The models were trained using pretrained ResNet50 architecture on MATLAB 2021b (MathWorks, Inc., Natick, MA, USA) for each image set (B-scan, retinal thickness, mid-retinal, EZ, and choroid). Selection of deep and shallow convolutional neural network (CNN) architectures was based on our previous studies on DL of OCT images for macular diseases 29 , 30 . To evaluate the performance of binodal imaging, two OCT images from each set underwent concatenation, and the resulting image was used for model training, validation, and testing.…”
Section: Methodsmentioning
confidence: 99%
“…The models were trained using pretrained ResNet50 architecture on MATLAB 2021b (MathWorks, Inc., Natick, MA, USA) for each image set (B-scan, retinal thickness, mid-retinal, EZ, and choroid). Selection of deep and shallow convolutional neural network (CNN) architectures was based on our previous studies on DL of OCT images for macular diseases 29 , 30 . To evaluate the performance of binodal imaging, two OCT images from each set underwent concatenation, and the resulting image was used for model training, validation, and testing.…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, most studies on CVI used a single horizontal OCT B-scan image. Since the choroidal pachy-vessels, defined as dilated outer choroidal vessels 17 19 , tend to enter the posterior pole with oblique pattern from the equator, the authors hypothesized that CVI values would differ depending on the radial scan direction. To our best knowledge, however, there has been no study comparing CVI according to scan directions of OCT B-scans.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al achieved 96.31% using ResNet50 to classify pachychoroid [161]. Lee et al used ResNet50 and Inception-v3 to simplify pachychoroid classification [111]. Hosoda et al used k-means clustering to categorize unilateral CNV patients, revealing AI's pattern discovery potential [120].…”
Section: ) Classification Of Multiple Pathologiesmentioning
confidence: 99%
“…vessel junctions in different imaging modalities, enabling direct comparisons and modalities registration[133]. Lee et al proposed a unique pipeline using proprietary software for Bruch's membrane segmentation, subsequently generating enface images for pachychoroid presence classification[111]. Miri et al demonstrated the use of an RF classifier for Bruch's membrane opening (BMO) segmentation in glaucoma patients' patients with CNV and pigmented retinitis[110].…”
mentioning
confidence: 99%